Simplifying the high-performance biomechanical assessment of high jump technique - Born, Z.; Goldacre, M.; Mundt, M.; Millett, E. L.; Phillips, E.; Alderson, J. (ISBS Proceedings Archive (Michigan), 2023)
A multitude of technical performance parameters are used to quantify high jump technique in the Australian high-performance environment, which can be time-consuming to measure and interpret. The purpose of this study was to investigate the efficacy of principal component analysis and stepwise multiple linear regression to simplify high-performance high jump biomechanical reports. Five non-intuitive principal components were derived, and three technical performance parameters (difference in knee angles during take-off contact, lean angle through hip at take-off contact, take-off foot contact time) influenced the height cleared by elite high jump athletes. This study establishes a method for simplifying high jump biomechanical reports and identifies the most important variables that contribute to high jump success.